Exosome-Transmitted lncARSR Promotes Sunitinib Resistance in Renal Cancer by Acting as a Competing Endogenous RNA - Qu, Le; Ding, Jin; Chen, Cheng; Wu, Zhen-Jie; Liu, Bing; Gao, Yi; Chen, Wei; Liu, Feng; Sun, Wen; Li, Xiao-Feng; Wang, Xue; Wang, Yue; et al. (Cancer cell, 2016)
Sunitinib resistance is a major challenge for advanced renal cell carcinoma (RCC). Understanding the underlying mechanisms and developing effective strategies against sunitinib resistance are highly desired in the clinic. Here we identified an lncRNA, named lncARSR (lncRNA Activated in RCC with Sunitinib Resistance), which correlated with clinically poor sunitinib response. lncARSR promoted sunitinib resistance via competitively binding miR-34/miR-449 to facilitate AXL and c-MET expression in RCC cells. Furthermore, bioactive lncARSR could be incorporated into exosomes and transmitted to sensitive cells, thus disseminating sunitinib resistance. Treatment of sunitinib-resistant RCC with locked nucleic acids targeting lncARSR or an AXL/c-MET inhibitor restored sunitinib response. Therefore, lncARSR may serve as a predictor and a potential therapeutic target for sunitinib resistance. [Display omitted] •lncARSR promotes sunitinib resistance and predicts poor response of RCC patients•Intercellular transfer of lncARSR by exosomes disseminates sunitinib resistance•lncARSR acts as a ceRNA for miR-34 and miR-449 to promote AXL and c-MET expression•Targeting lncARSR or AXL/c-MET in sunitinib-resistant RCC restores drug sensitivity Qu et al. identify lncARSR as a mediator of sunitinib resistance in renal cell carcinoma by acting as a competing endogenous RNA for miR-34 and miR-449, thereby increasing expression of their targets AXL and c-MET, and show that exosome-mediated transmission of lncARSR can confer resistance to sensitive cells.